2007
DOI: 10.22401/jnus.10.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism Studies of Oxidation of Α-Amino Acids by N-Bromosuccinimide

Abstract: Kinetics and mechanism studies of oxidation of some α-amino acids (Proline, Arginine, Alanine) (AA) by N-Bromosuccinimide (NBS) by using conductivity method was carried out. The kinetic study showed that the reaction was first order with respect to NBS and AA. The effect of addition of HClO 4 to the reaction was negative on the rate of reaction. The reaction was carried outwere calculated. The rate of reaction of AA was as follows: Proline > Arginine > Alanine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…19 A kinetic study and the determination of the thermodynamic parameters of α-amino acids (proline, arginine, alanine) oxidised by NBS were carried out by Mohammed and Hadi, and the results obtained indicated that for both oxidation of creatine (AA) and NBS the reaction was first-order. 20 A kinetic study of the oxidative cleavage reaction of gabapentin with NBS conducted by Bhandarkar and Mohana indicated that the reaction was a first-order kinetic reaction. 21 Yadav et al studied the oxidation of L-valine by NBS and found the reaction was a first-order kinetics reaction with respect to L-valine.…”
Section: Introductionmentioning
confidence: 99%
“…19 A kinetic study and the determination of the thermodynamic parameters of α-amino acids (proline, arginine, alanine) oxidised by NBS were carried out by Mohammed and Hadi, and the results obtained indicated that for both oxidation of creatine (AA) and NBS the reaction was first-order. 20 A kinetic study of the oxidative cleavage reaction of gabapentin with NBS conducted by Bhandarkar and Mohana indicated that the reaction was a first-order kinetic reaction. 21 Yadav et al studied the oxidation of L-valine by NBS and found the reaction was a first-order kinetics reaction with respect to L-valine.…”
Section: Introductionmentioning
confidence: 99%